Enhancing Communicative Competence through Learner-Centered Approach in SMK Pharmacy Surabaya: A Study on Merdeka Curriculum Implementation - Arkananta, Jonathan Abnerio; Rahman, Gohar (Sinergi International Journal of Education, 2024)
This research provides an overview of Indonesia's education system, focusing on the 2022 (Merdeka Curriculum) and its emphasis on developing competencies and skills such as critical thinking, problem-solving, creativity, and collaboration. The research discusses the role of the curriculum in the teaching and learning process. It highlights the Learner-centered Approach as a comprehensive framework for designing English language learning activities through project-based learning (PBL). The study also examines Communicative Language Teaching (CLT) as a complementary approach to the Merdeka Curriculum in English language learning. The study uses a qualitative approach to investigate the effectiveness of communicative language teaching on the Merdeka Curriculum on SMK Farmasi Surabaya teaching and learning activity, with data collected through observations and interviews with students and teachers. The findings of this study will provide insights for language educators on the potential benefits of integrating communicative language teaching to enhance language learning outcomes.